THE IMPORTANCE OF LINGUISTIC AND COGNITIVE APPROACHES IN THE VERBALIZATION OF HUMAN BEHAVIOR - Shakhnoza Erkinovna Ergasheva (International Journal of Literature and Language Studies, 2026)
The study of human behavior has become one of the main issues in modern linguistics due to the anthropocentric orientation of contemporary language research. Human behavior is represented and perceived through linguistic means, particularly through lexical and grammatical units that encode actions, emotions, intentions, and social interactions. This article examines the significance of linguistic and cognitive approaches in the verbalization of human behavior. The research points out the role of language as a tool for representing behavioral patterns and explores the cognitive mechanisms underlying the conceptualization of behavior. By integrating linguistic and cognitive perspectives, the study demonstrates how language reflects cultural values, social norms, and individual experiences. The findings reveal that behavior-related linguistic units serve not only communicative functions but also cognitive and cultural functions, contributing to the formation of a linguistic worldview.